2021
DOI: 10.1016/j.labeco.2021.102080
|View full text |Cite
|
Sign up to set email alerts
|

Losing in a boom: Long-term consequences of a local economic shock for female labour market outcomes

Abstract: This paper examines the long-term labour market consequences of a positive economic shock, the first discovery of oil and gas in Norway. Existing studies focus on the short-term and men, while less is known about women and the persistence of such shocks. Oil discovery increased male earnings (by 7%), while female earnings declined (by 10%). These shifts persist for two decades. Labour force participation and occupational change account for the earnings divergence. Within married couples, wives' earnings declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Using data from Norway, Bennett et al (2021) also proved that as a result of a long-term positive economic shock-a discovery of oil and gas in 1969-male workers' income has increased by 7%, whereas female income has decreased by up to 14%. Kikuchi et al (2021) found that COVID-19's effects on the Japanese labour market vary between women and men, with an amplified severe effect on the former.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…Using data from Norway, Bennett et al (2021) also proved that as a result of a long-term positive economic shock-a discovery of oil and gas in 1969-male workers' income has increased by 7%, whereas female income has decreased by up to 14%. Kikuchi et al (2021) found that COVID-19's effects on the Japanese labour market vary between women and men, with an amplified severe effect on the former.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Using data from the United States, United Kingdom, Italy, Japan, South Korea, and China, Dang and Nguyen ( 2021 ) found that women were 24% more likely than men to permanently lose their jobs, and women should expect their labour income to fall by 50% more than that of men. Using data from Norway, Bennett et al ( 2021 ) also proved that as a result of a long‐term positive economic shock—a discovery of oil and gas in 1969—male workers' income has increased by 7%, whereas female income has decreased by up to 14%. Kikuchi et al ( 2021 ) found that COVID‐19's effects on the Japanese labour market vary between women and men, with an amplified severe effect on the former.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, as the oil industry developed over time, high-skilled opportunities also grew. In addition, the labour market impacts of the oil boom also differ between men and women (Kearney and Wilson, 2018;Bennett, Ravetti and Wong, 2021). Figure 6 presents the evolution of inequality over time between high and low oil areas for men (panel a) and women (panel b).…”
Section: The Relationship Between Oil and Inequalitymentioning
confidence: 99%
“…However, as the oil industry developed over time, high‐skilled opportunities also grew. In addition, the labour market impacts of the oil boom also differ between men and women (Kearney and Wilson, 2018; Bennett, Ravetti and Wong, 2021).…”
Section: Relating Labour Market Trends To Low Levels Of Overall Inequ...mentioning
confidence: 99%
“…Another category of previous research findings refers to the impact of crises on firms in general or on small- and medium-sized enterprises. In this context, regarding the financial crisis of 2008–2009, the main effects identified in the literature at the level of companies refer to: the impact on human resources (employment/unemployment, poverty, migrant workers, child labor) [ [32] , [33] , [34] ], and the financial difficulties generated, such as depreciation [ [35] , [36] , [37] ].…”
Section: Literature Reviewmentioning
confidence: 99%